Improved Formulation of 224Ra-Labeled Calcium Carbonate Microparticles by Surface Layer Encapsulation and Addition of EDTMP - Ruth Gong Li; Kim Lindland; Sandra Karen Tonstad; Tina Bjørnlund Bønsdorff; Asta Juzeniene; Sara Westrøm; Roy Hartvig Larsen (MDPI AG, 2021)
Radium-224-labeled CaCO3 microparticles have been developed to treat peritoneal carcinomatosis. The microparticles function as carriers of 224Ra, facilitating intraperitoneal retention of the alpha-emitting radionuclide. It was necessary to control the size of microparticles in suspension over time and introduce a sterilization process for the clinical use of the radiopharmaceutical. Ethylenediamine tetra(methylene phosphonic acid) (EDTMP) was investigated as a stabilizing additive. The possibility of encapsulating the radiolabeled microparticles with an outer surface layer of CaCO3 for the improved retention of radioactivity by the carrier was studied. This work evaluated these steps of optimization and their effect on radiochemical purity, the biodistribution of radionuclides, and therapeutic efficacy. An EDTMP concentration of >1% (w/w) relative to CaCO3 stabilized the particle size for at least one week. Without EDTMP, the median particle size increased from ~5 µm to ~25 µm immediately after sterilization by autoclaving, and the larger microparticles sedimented rapidly in suspension. The percentage of adsorbed 224Ra progeny 212Pb increased from 56% to 94% at 2.4-2.5% (w/w) EDTMP when the 224Ra-labeled microparticles were layer-encapsulated. The improved formulation also resulted in a suitable biodistribution of radionuclides in mice, as well as a survival benefit for mice with intraperitoneal ovarian or colorectal tumors.